2001
DOI: 10.1159/000063460
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Familial Endocrine Neoplasia Syndromes in Children

Abstract: Familial endocrine neoplasia syndromes multiple endocrine neoplasia (MEN) type 1, MEN type 2 and von Hippel Lindau (VHL) can now be diagnosed genetically in childhood. Paediatric endocrinologists must therefore be prepared to investigate and manage these children. This paper provides an overview of the major features of these syndromes and suggests protocols for regular screening of children known to be at risk of developing these disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 23 publications
1
9
0
2
Order By: Relevance
“…Pancreatic insulinoma has been described in a 7-year-old boy (24), followed by primary hyperparathyroidism at the age of 8 years (3). Our index patient showed an insulinoma when he was 8 years old, reinforcing the proposition that a clinical screening program for children carrying MEN1 gene mutations should start at the age of 10-15 years (21,22,25,26). These children should be evaluated with annual blood tests by measuring serum calcium, pancreatic polypeptide and gastrin, prolactin and insulin-like growth factor-1.…”
Section: Discussionsupporting
confidence: 64%
“…Pancreatic insulinoma has been described in a 7-year-old boy (24), followed by primary hyperparathyroidism at the age of 8 years (3). Our index patient showed an insulinoma when he was 8 years old, reinforcing the proposition that a clinical screening program for children carrying MEN1 gene mutations should start at the age of 10-15 years (21,22,25,26). These children should be evaluated with annual blood tests by measuring serum calcium, pancreatic polypeptide and gastrin, prolactin and insulin-like growth factor-1.…”
Section: Discussionsupporting
confidence: 64%
“…The role of menin has not yet been fully elucidated; it is a nuclear protein which interacts with the AP1 transcription factor JunD [9] and other factors related to transcriptional regulation and cell cycle control as well as Smad3 [10]. Recommendations for MEN1 mutation testing are being developed in order to manage the diagnosis of this syndrome [11] in the hope that early disease recognition can prevent certain types of morbidity [12]. Mutation detection by sequencing is time-consuming, because mutations are spread right across the gene.…”
Section: Introductionmentioning
confidence: 99%
“…A pancreatic insulinoma has been described in a 7-year-old boy (23), and primary hyperparathyroidism from the age of 8 years (24). Johnston et al (25,26) suggested a screening programme for children carrying MEN1 gene mutations, to start at the age of 10 -15 years. These children should be screened with annual blood tests measuring serum calcium, pancreatic polypeptide and gastrin, prolactin and insulin-like growth factor-1.…”
Section: Discussionmentioning
confidence: 99%